2018
DOI: 10.17221/526/2018-pse
|View full text |Cite
|
Sign up to set email alerts
|

Low phosphorus availability increases shoot boron concentration in canola and potato but not in wheat

Abstract: A large proportion of global agricultural soils contain suboptimal available phosphorus (P) for the growth of many plant species. Boron (B) plays important roles in plant growth and development, but limited research has been conducted to study B uptake under low P availability. This study comprised a hydroponic and a mini-rhizobox experiment with canola (Brassica napus L.), potato (Solanum tuberosum L.) and wheat (Triticum aestivum L.) under P sufficient and deficient conditions. Boron concentrations, rhizosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
4
0
0
Order By: Relevance
“…This Si-mediated improvement of leaf P status could have further led to some complex changes in the uptake and accumulation of other nutrients. For instance, Wang et al. (2018) showed that P-deficiency stimulated increased B uptake in dicots (which have intrinsically higher B requirements), but not in monocots, what is in accordance with our findings in pedunculate oak ( Figures 6A , 7A ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This Si-mediated improvement of leaf P status could have further led to some complex changes in the uptake and accumulation of other nutrients. For instance, Wang et al. (2018) showed that P-deficiency stimulated increased B uptake in dicots (which have intrinsically higher B requirements), but not in monocots, what is in accordance with our findings in pedunculate oak ( Figures 6A , 7A ).…”
Section: Discussionsupporting
confidence: 91%
“…This Si-mediated improvement of leaf P status could have further led to some complex changes in the uptake and accumulation of other nutrients. For instance, Wang et al (2018) showed P-deficiency stimulated increased B uptake in dicots (which have intrinsically higher B requirements), but not in monocots, what is in accordance with our findings in pedunculate oak (Figures 6A, 7A). In both rhizobox and hydroponic experiments, these authors demonstrated the up-regulation of BnBOR1 transporter in oilseed rape by the lack of P. We further showed that when plant P status was improved by Si addition (Figure 6A), the uptake and leaf accumulation of B was decreased (Table 4; Figure 7A).…”
Section: Responses To P Deficiencysupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that not only is P concentration significantly affected by B status (deficiency or toxicity), but B concentration is also dramatically influenced by P availability (Wang et al, 2018;Zhou et al, 2014). In this study, the P concentration significantly decreased in all organs of the seedlings under B-deficient conditions, particularly in the leaf at pH 6.0 ( Fig.…”
Section: Discussionsupporting
confidence: 53%